Thiamine and spinocerebellar ataxia type 2 - Costantini, Antonio (BMJ Publishing Group, 2013)
Spinocerebellar ataxia type 2 is a genetic disorder characterised by the degeneration of the cerebellum, its connections and degeneration in brainstem areas. Some observations indicate that high doses of thiamine may lead to the partial regression of the symptoms. One patient was under rehabilitative treatment from June 2011 to July 2012. We assessed the level of fatigue using the Fatigue Severity Scale. We performed the Scale for Assessment and Rating of Ataxia and Robertson Profile for Dysarthria (Italian version). Thiamine and thiamine pyrophosphate levels in the blood were within the healthy reference range. We started a parenteral therapy with 100 mg intramuscular every 7 days. The therapy led to a partial regression of fatigue within a few days. After about 3 months, a discreet improvement of motor symptoms especially in speech was observed. The symptoms could derive from a focal thiamine deficiency that could determine a selective neuronal loss.